‘Do not try to outsource dirty business into your value chain’: an interview with Matthias Kleinhempel - Klinkhammer, Julian (Bribery, fraud, cheating, 2020)
Julian Klinkhammer: Mr Kleinhempel, you have provided your audience and discussants at the Herrenhausen Symposium with a knowledgeable perspective on the mechanisms of anti-corruption, based on your vast experience in South American Markets and in executive education. In hindsight, what was the most surprising insight with regard to anti-corruption that you have gained through your participation?
Gesehen am 16.03.2023